On the haem auxotrophy of the soft tick Ornithodoros moubata - Hatalová, Tereza; Erhart, Jan; Kopáček, Petr; Perner, Jan (Ticks and tick-borne diseases, 2023)
Genomes of ticks display reductions, to various extents, in genetic coding for enzymes of the haem biosynthetic pathway. Here, we mined available transcriptomes of soft tick species and identified transcripts encoding only half of the enzymes involved in haem biosynthesis. Transcripts identified across most species examined were those coding for porphobilinogen synthase, coproporphyrinogen oxidase, protoporphyrinogen oxidase, and ferrochelatase. Genomic retention of porphobilinogen synthase seems to be soft tick-restricted as no such homologue has been identified in any hard tick species. Bioinformatic mining is thus strongly indicative of the lack of biochemical capacity for de novo haem biosynthesis, suggesting a requirement for dietary haem. In the hard tick Ixodes ricinus, depletion of dietary haem, i.e. serum feeding, leads to oviposition of haem-free eggs, with no apparent embryogenesis and larvae formation. In this work, we show that serum-fed Ornithodoros moubata females, unlike those of I. ricinus, laid haem-containing eggs similarly to blood-fed controls, but only by a small proportion of the serum-fed females. To enhance the effect of dietary haem depletion, O. moubata ticks were serum-fed consecutively as last nymphal instars and females. These females laid eggs with profoundly reduced haem deposits, confirming the host origin of the haem. These data confirm the ability of soft ticks to take up and allocate host haem to their eggs in order to drive reproduction of the ticks.
Keywords: hem; Porphobilinogen Synthase; Parasitism; Argasidae; ženské pohlaví; Haem biosynthesis; Soft ticks; zvířata; Membrane feeding; Ornithogalum; Female; Ixodidae; Ornithodoros; Porphobilinogen synthase; Heme; porfobilinogensynthasa; Animals